INFORMATION SYSTEM OF COMMUNITY SERVICES IN THE LAND OFFICE OF CENTRAL LAMPUNG REGENCY - Mirantika, Fika; Apsiswanto, Untoro; Saputri, Tri Aristi (STMIK DHARMA WACANA, 2023)
Badan Pertanahan Nasional Kabupaten Lampung Tengah City (BPN) is a government organization specializing in land certificates services for general public. With The system currently operated is not working optimally. That can be seen from the delay in processing data. This is because BPN Kabupaten Lampung Tengah doesn’t use database in its system. Besides,without the use of database can causing Double land certificate problem thats been happening in the past. Therefore, it needs a solution in its system that can overcome the problem, facilitate BPN Kabupaten Lampung Tengah in accomplishing its duties by using application program that can accelerate certificate processing services. The writer uses Science based research method on available theory and the research design in study type, whereas data collection methods were interview, observation, and literature study related to the investigated problem. The system development model used was waterfall and by structural approach method with aids such as flowmap, DFD, etc. The writer tried to propose a solution where improvement was conducted on database that facilitates BPN Kabupaten Lampung Tengah conducting land certificates processing services. This approach was in conformity with necessity in building or designing an alternative land certificate information system Using Web and localhost server for application program. The finding of this research was alternative Land Certificate proccessing system that could overcome the mentioned problem by using database so that data searching process becomes easier and quicker. The data base system could also minimize user errors, and report preparation becomes more efficient and can be accessed at any time. The weakness of this research was that not online, whereas its advantage was the achievement of all stated goals and limitations.